Perkembangan dan Aplikasi Biomaterial dalam Bidang Kedokteran Modern: A Review - Irza Sukmana; Ahmad Yudi Eka Risano; Mahruri Arif Wicaksono; Rizal Adi Saputra (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
The medical device market in Indonesia experiences growth every year, Indonesia implements imports of medical devices. Indonesia has many experts in the field of medical devices and their production processes, at university, research institutions and other government institutions. The government provides multi-year grants for research on biomaterials and medical devices. Materials to make medical devices are called biomaterials. Biomaterials can be defined as synthetic materials that interact directly with living bodies in the form of implants or as medical devices. Biomaterials can function to repair, replace, support and or restore parts of the human body. Biomaterials have undergone many developments, types of biomaterials, advanced biomaterials adapted to applications in the medical field. Biomaterials can be in the form of metals, ceramics, polymers or composites with research that continues to advance and be developed. This paper aims to highlight types and application of biomaterials in the medical field as well as the potential application of advanced biomaterials in the future.